PENGEMBANGAN MODUL PEMBELAJARAN TEKS PROSEDUR BERBASIS MODEL DISCOVERY LEARNING DI SMP KELAS VII - Ayu Setiyo Putri; Iswanti Wahyuni; Bambang Riadi (FKIP Universitas Lampung, 2021)
This research was This research aims to produce, develop, and describe the feasibility of teaching material product in the form of discovery learning-based procedure text learning module in SMP class VII. This research used the Research and Development (RD) method by Borg and Gall. The product research results in the form of modules which consists of four modules containing learning materials, learning activities, practice questions, summaries, and formative tests. Each module has learning activities by implementing the steps in the discovery learning model, namely providing stimulation, identifying problems, collecting data, processing data, verifying data, and drawing conclusions. The module feasibility test was carried out by material expert and educator of Indonesian subject. The results of the validation test by material expert obtained an average percentage of 81.25% in very feasible category. The results of validation by Indonesian language educator obtained an average percentage of 82.5% in very feasible category. Penelitian ini bertujuan untuk menghasilkan, mengembangkan, dan mendeskripsikan kelayakan produk bahan ajar berupa modul pembelajaran teks prosedur berbasis discovery learning di SMP kelas VII. Penelitian ini menggunakan metode Research and Development (RD) oleh Borg dan Gall. Hasil penelitian produk berupa modul yang dihasilkan terdiri atas empat modul memuat materi pembelajaran, kegiatan belajar, latihan soal, rangkuman, dan tes formatif. Pada modul memiliki kegiatan belajar yang mengimplementasikan langkah-langkah dalam model discovery learning. Uji kelayakan modul dilakukan oleh ahli materi dan pendidik mata pelajaran bahasa Indonesia. Hasil uji validasi oleh ahli materi diperoleh rerata persentase 81,25% berkategori sangat layak. Hasil validasi oleh pendidik bahasa Indonesia diperoleh rerata persentase 82,5% berkategori sangat layak.Keywords: teaching materials, discovery learning, module, procedure textDOI: http://dx.doi.org/10.23960/Kata.v9.i2.202106